PENGARUH INFLUENCER MARKETING DAN IKLAN TERHADAP BRAND AWARENESS SKINCARE SKINTIFIC DI KOTA BANJARMASIN - Annisa Salsabela; Nurul Wahyuni; Irwansyah; M. Hasanur Arifin (Business Administration, FISIP ULM, 2025)
The Influence of Influencer Marketing and Advertising on Brand Awareness of Skintific Skincare in Banjarmasin City. This study aims to examine the partial and simultaneous effects of influencer marketing and advertising on brand awareness of Skintific skincare in Banjarmasin City.This study uses a quantitative approach, with the research location in Banjarmasin City. A sample of 100 respondents who are familiar with Skintific skincare in Banjarmasin City was selected using non-probability sampling with purposive sampling. Data analysis was performed using multiple linear regression. The results of this study prove that Influencer Marketing has a significant influence on Brand Awareness of Skincare Skintific in Banjarmasin City. Advertising has a significant influence on Brand Awareness of Skincare Skintific in Banjarmasin City. Additionally, Influencer Marketing and Advertising have a significant influence on Brand Awareness of Skincare Skintific in Banjarmasin City.